'I just want someone to rub some life into them!': the lived experience of impaired sensation in the feet related to multiple sclerosis. (1st January 2021) - Cook, Claire; Vuoskoski, Pirjo
Abstract : Background: Impaired sensation in the feet is a commonly reported symptom experienced by people with multiple sclerosis. Aim: To explore the lived experiences of people living with multiple sclerosis-related impaired sensation in their feet. Method: Five open, unstructured interviews were analysed using a descriptive phenomenological method developed by Amedeo Giorgi. Findings: The essential structure of the research phenomenon consists of six key constituents: sense of heightened awareness of body sensation; sense of changed relationship to the feet; sense of changed participation in daily life; sense of the self with multiple sclerosis; sense of the meaning of interaction with others; and sense of being with impaired sensation. Conclusions: Findings imply that the experience of impaired sensation in the feet related to multiple sclerosis is a complex, lived-through phenomenon, interrelated to other aspects experienced with the condition. Clinicians are encouraged to consider implications of the phenomenon during encounters with people with multiple sclerosis, being well-placed to provide meaningful support.